Determinan Praktik Tax avoidance pada Perusahaan Sektor Consumer non-cyclicals yang Terdaftar di BEI - Erindanindya, Fara Navy; Mustafida, Nurul (Universitas Muhammadiyah Gresik, 2024)
Taxes are commitments that must be paid so that the government can continue to implement national development planning without causing a direct imbalance for taxpayers. Taxes have two different points of view. From the company’s perspective as a taxpayer, taxes are considered a burden that will reduce net profit. This study is motivated by the decline in tax revenues from the processing industry, losses both globally and in Indonesia due to tax avoidance practices, as well as the phenomenon of companies engaging in tax avoidance. This study analyses the effect of institutional ownership, Capital intensity, and Corporate Social Responsibility disclosure on tax avoidance. This study used a quantitative method with secondary data from financial, annual, and sustainability reports of non-cyclical consumer sector companies listed on the IDX for the 2018-2022 periods. Sampling was carried out using a simple random sampling method with a total sample of 288 company data points. Data were analyzed using descriptive statistical analysis, logistic regression analysis, and hypothesis testing with the help of SPSS 26 software. The results of this study show that institutional ownership and Capital intensity do not affect tax avoidance, while Corporate Social Responsibility disclosure affects tax avoidance.